2021
DOI: 10.1177/09544054211043484
|View full text |Cite
|
Sign up to set email alerts
|

Multicut technology used in WEDM machining of Mar-M247

Abstract: Wire electrical discharge machining (WEDM) technology is often used for the final machining of parts to the required surface quality without further finishing operations. At the same time, WEDM has a significant advantage over other machining technologies, and in the fact, it is possible to machine all materials, regardless of their hardness or toughness, it only needs to be at least electrically conductive. Aviation nickel superalloy Mar-M247, which is usually machined to the final form by parts using WEDM, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The cutting speed is a very important parameter in unconventional wire cutting technology, because it cannot be easily set when programming the machine, but is controlled by the machine itself, which regulates this speed itself based on parameter settings so that the tool was machined with the setting of machine parameters: U = 50 V, T on = 10 ms, T off = 30 ms, v = 14 m/min and I = 35 A. This maximum cutting speed is slightly higher than that observed on the contrary when machining Hadfield steel with the same material thickness, which was presented in the Mouralova et al 8 study. In contrast, when machining AISI 4140 steel of the same thickness, the speed was significantly lower, which was presented in the Tosun 24 or Datta and Mahapatra 25 studies.…”
Section: Evaluation Of the Cutting Speedmentioning
confidence: 83%
See 1 more Smart Citation
“…The cutting speed is a very important parameter in unconventional wire cutting technology, because it cannot be easily set when programming the machine, but is controlled by the machine itself, which regulates this speed itself based on parameter settings so that the tool was machined with the setting of machine parameters: U = 50 V, T on = 10 ms, T off = 30 ms, v = 14 m/min and I = 35 A. This maximum cutting speed is slightly higher than that observed on the contrary when machining Hadfield steel with the same material thickness, which was presented in the Mouralova et al 8 study. In contrast, when machining AISI 4140 steel of the same thickness, the speed was significantly lower, which was presented in the Tosun 24 or Datta and Mahapatra 25 studies.…”
Section: Evaluation Of the Cutting Speedmentioning
confidence: 83%
“…The occurrence of defects is a major shortcoming affecting the expected life or proper functionality of the component. This study builds on and draws on the findings of previous studies on WEDM machining of individual materials such as Hardox, 7 Mar-M247, 8 Creusabro, 9 nickel alloy B1914 10 or aluminium alloy 7475-T7351. 11 The findings presented in this study will be used primarily for the development of WEDM machining in the aerospace, automotive and energy industries.…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al [21] studied the effects of different WEDM cutting times on the surface microstructure of a NiTi shape memory alloy, and the results showed that after multiple trims, the recast layer of the samples was effectively controlled. Mouralova et al [22] investigated the effect of multiple WEDM processes on surface quality and found that multiple processing can reduce the microcracks on the surface.…”
Section: Introductionmentioning
confidence: 99%